2018
DOI: 10.17159/2078-516x/2018/v30i1a4947
|View full text |Cite
|
Sign up to set email alerts
|

The impact of anterior knee pain on the quality of life among runners in Ekurhuleni, Gauteng

Abstract: Background: Anterior knee pain (AKP) is the most common injury among runners and has a negative impact on the quality of life (QOL) of many athletes. Objective: To determine the impact of anterior knee pain on the QOL among runners in Ekurhuleni, Gauteng. Materials & methods: A cross–sectional study design was used. A population of 73 runners with AKP were included. Participants included runners aged 13 to 55-year-old. The SF-36 questionnaire was used to collect data. Ethical clearance, permission from clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Studies have shown that runners in under-resourced communities have a high prevalence of poorly managed PFP injuries because of inaccessible, unaffordable, unavailable and inadequate rehabilitation services (Kunene et al 2018a(Kunene et al , 2018b(Kunene et al , 2019(Kunene et al , 2020a(Kunene et al , 2020b. South Africa faces the challenge of scarce healthcare resources, especially in low socio-economic communities, which makes it difficult to fully address the health-related needs of people (Rasool & Both 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that runners in under-resourced communities have a high prevalence of poorly managed PFP injuries because of inaccessible, unaffordable, unavailable and inadequate rehabilitation services (Kunene et al 2018a(Kunene et al , 2018b(Kunene et al , 2019(Kunene et al , 2020a(Kunene et al , 2020b. South Africa faces the challenge of scarce healthcare resources, especially in low socio-economic communities, which makes it difficult to fully address the health-related needs of people (Rasool & Both 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Round 1: Evidence from relevant articles was used to generate 32 statement items (five core items and 27 sub-items) on how rehabilitation programmes for runners with PFP can be implemented in under-resourced communities. In addition, the outcome from studies on the nature of PFP, runners' needs in under-resourced communities and current rehabilitation strategies were also used (Kunene et al 2018a(Kunene et al , 2018b(Kunene et al , 2019(Kunene et al , 2020a(Kunene et al , 2020b. The 32 preliminary statement items were converted into a questionnaire and pilot tested amongst three sports medicine academics, one sports physician and one clinical physiotherapist.…”
Section: The Delphi Process Included Three Roundsmentioning
confidence: 99%
See 1 more Smart Citation
“…insoles) should be carried out. Kunene et al (2018b) recommend in their studies that a comprehensive rehabilitation programme should encompass the physical and non-physical components of AKP to improve the QoL for runners. For this to be achieved, a multimodal rehabilitation programme may need to be designed for runners.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study highlighted the negative impact of AKP on the QOL of runners from underresourced communities, recommending the need to address the non-physical features when formulating strategies to improve QOL among the running population with AKP. [5] Runners can be predisposed to AKP through intrinsic and external factors. Intrinsic factors may include a weak vastus medialis oblique, tight gastrocnemius-soleus muscle complex, dysfunction of the hip muscles, foot pronation, generalised joint laxity, limb length discrepancy, patellar malalignment and patellar hypermobility.…”
mentioning
confidence: 99%